Direct induction of autophagy by Atg1 inhibits cell growth and induces apoptotic cell death. - Scott, R.C.; Juhasz, G.; Neufeld, T.P. (Current Biology, 2007)
To survive starvation and other forms of stress, eukaryotic cells undergo a lysosomal process of cytoplasmic degradation known as autophagy. Autophagy has been implicated in a number of cellular and developmental processes, including cell-growth control and programmed cell death. However, direct evidence of a causal role for autophagy in these processes is lacking, resulting in part from the pleiotropic effects of signaling molecules such as TOR that regulate autophagy. Here, we circumvent this difficulty by directly manipulating autophagy rates in Drosophila through the autophagy-specific protein kinase Atg1.We find that overexpression of Atg1 is sufficient to induce high levels of autophagy, the first such demonstration among wild-type Atg proteins. In contrast to findings in yeast, induction of autophagy by Atg1 is dependent on its kinase activity. We find that cells with high levels of Atg1-induced autophagy are rapidly eliminated, demonstrating that autophagy is capable of inducing cell death. However, this cell death is caspase dependent and displays DNA fragmentation, suggesting that autophagy represents an alternative induction of apoptosis, rather than a distinct form of cell death. In addition, we demonstrate that Atg1-induced autophagy strongly inhibits cell growth and that Atg1 mutant cells have a relative growth advantage under conditions of reduced TOR signaling. Finally, we show that Atg1 expression results in negative feedback on the activity of TOR itself.Our results reveal a central role for Atg1 in mounting a coordinated autophagic response and demonstrate that autophagy has the capacity to induce cell death. Furthermore, this work identifies autophagy as a critical mechanism by which inhibition of TOR signaling leads to reduced cell growth.